Determinação do coeficiente de cultura (Kc) para o manejo da água e domesticação do Camu-camu (Myrciaria dubia (Kunth McVaugh) em terra firme - Rodriguez, Carlos Abanto (2020)
Camu-camu is a genetic resource in the Amazon with great potential for use due to its nutraceutical properties, however, as it is a culture in the process of domestication techniques that assist in ex situ adaptation, must be eveloped. In this sense, the objective was to determine the crop coefficient (Kc) for water management and domestication of camu-camu (Myrciaria dubia (Kunth) McVaugh) on uplands, both by the methods of lysimetry and by indirect measurement of humidity in final field; in the first, drainage lysimeters were used and in the second, calibrated soil moisture sensors (10HS®) were used. For both methods, 6 camu-camu plants were used, each with 2, 4 and 6 years of age with similar characteristics in height, leaf area, stem diameter and number of basal and terminal branches. Soon, in a plant of each age, a vegetable mulch (VM) composed of remains of Trachypogon plumosus grass was placed in the area of influence of the crown in order to determine the effects on water consumption with and without VM. To determine Kc, it was necessary to calculate ETo by the Penman-Monteith/FAO method, and ETc by the water balance in the lysimeters and in the final field. After two years of evaluations (June 2017 to June 2019) it was possible to obtain water consumption in plants with 2, 3, 4, 5, 6 and 7 years, because, chronologically, they reached another year of age. The Kc determined with both methods showed similar values up to 6 years of age with and without VM. On the contrary, in plants with 7 years it was observed that the values determined in the lysimeters were superior to those verified with 10HS® sensors, because the size of the lysimeter was not big enough to support the development of the root system of the plants of 7 years of age. For this reason, the Kc of plants with VM up to 6 years of age can be used as a reference in both methods, but for the seventh year of maximum fruiting onwards, the Kc obtained by the second method studied with VM is recommended.